GlyT1 Inhibitor NFPS Exerts Neuroprotection via GlyR Alpha1 Subunit in the Rat Model of Transient Focal Cerebral Ischaemia and Reperfusion - Baosheng Huang; Qingsong Xie; Xiaocheng Lu; Tengda Qian; Shuai Li; Ronglan Zhu; Wan Yu; Gong Chen; Zheng Chen; Xinlong Xu; Tianlu Wang; Lixin Li (Cellular Physiology and Biochemistry, 2016)
Background/Aims: Glycine is a strychnine-sensitive inhibitory neurotransmitter in the central nervous system (CNS), especially in the spinal cord, brainstem, and retina. The objective of the present study was to investigate the potential neuroprotective effects of GlyT1 inhibitor N [3-(4'-fluorophenyl)-3-(4'-phenylphenoxy) propyl] sarcosine (NFPS) in the rat model of experimental stroke. Methods: In vivo ischaemia was induced by transient middle cerebral artery occlusion (tMCAO). The methods of Western Blotting, Nissl Staining and Morris water maze methods were applied to analyze the anti-ischaemia mechanism. Results: The results showed that high dose of NFPS (H-NFPS) significantly reduced infarct volume, neuronal injury and the expression of cleaved caspase-3, enhanced Bcl-2/Bax, and improved spatial learning deficits which were administered three hours after transient middle cerebral artery occlusion (tMCAO) induction in rats, while, low dose of NFPS (L-NFPS) exacerbated the injury of ischaemia. These findings suggested that low and high dose of NFPS produced opposite effects. Importantly, it was demonstrated that H-NFPS-dependent neuronal protection was inverted by salicylate (Sal), a specific GlyR ɑ1 antagonist. Such effects could probably be attributed to the enhanced glycine level in both synaptic and extrasynaptic clefts and the subsequently altered extrasynaptic GlyRs and their subtypes. Conclusions: These data imply that GlyT1 inhibitor NFPS may be a novel target for clinical treatment of transient focal cerebral ischaemia and reperfusion which are associated with altered GlyR alpha 1 subunits.